Influence of knowledge of sprint number on pacing during repeated-sprint exercise - Billaut, F.; Bishop, D. J.; Schaerz, S.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The anticipation of exercise-induced stress influences performance during continuous exercise. However, not all exercise is continuous. This study explores the influence of prior knowledge of sprint number on mechanical work, surface EMG, and RPE during repeated-sprint exercise (RSE).